The anatomy of consumption in a household foreign currency debt crisis - Gyîozîo Gyöngyösi; Judit Rariga; Emil Verner (European Central Bank (ECB), 2022)
How do households adjust to a large debt shock? This paper studies household responses to a revaluation of foreign currency household debt during a large depreciation in Hungary. Relative to similar local currency debtors, foreign currency debtors reduce consumption expenditures approximately one-for-one with increased debt service, suggesting binding liquidity constraints. Foreign currency debtors reduce both the quantity and quality of expenditures, consistent with nonhomothetic preferences and a "flight from quality." Debt revaluation has no effect on labor market status, hours, or earnings, but there is a small adjustment toward foreign income streams and a substantial increase in home production.
Keywords: E21; G51; J20; 330; Marginal propensity to consume; flight from quality; home production